An Effort to Isolate Mycobacterium bovis from Environmental Substrates during Investigations of Bovine Tuberculosis Transmission Sites (Cattle Farms and Wildlife Areas) in Michigan, USA. (22nd September 2011) - Fine, Amanda E.; O'Brien, Daniel J.; Winterstein, Scott R.; Kaneene, John B.
Abstract : Deer movements on cattle farms, wildlife feeding, and livestock management practices in Michigan are thought to create opportunities for indirect transmission of Mycobacterium bovis via environmental substrates. To confirm the presence of viable M. bovis in the environment, substrates were collected from 13 farms with culture-confirmed M. bovis in cattle and 5 sites with high prevalence of M. bovis in free-ranging deer. None of the samples processed for mycobacterial culture were positive for M. bovis . Agent, host, and landscape-level factors decrease the probability of detecting M. bovis in the environment using conventional mycobacterial culture. Molecular techniques that increase the probability of M. bovis detection in environmental substrates should be applied to known sites of M. bovis transmission in Michigan. In the interim, epidemiological investigations informed by experimental studies will be most effective in characterizing M. bovis persistence in the environment and its role in the indirect interspecies transmission of M. bovis .